Aloneliness predicts relational anger and aggression toward romantic partners. Issue 5 (12th July 2022) - Swets, Julie A.; Cox, Cathy R.
Abstract: Aloneliness is the negative psychological state characterized by dissatisfaction with one's lack of solitude, which is connected to well‐being deficits (e.g., depression, stress). From an I 3 theory perspective, we expected that aloneliness could predict anger and partner‐directed aggression among persons in romantic relationships, who must, by nature of their partnership, dedicate time to their romantic partners. In Studies 1a and 1b ( N = 554), trait aloneliness positively correlated with trait anger, aggression, and violence, but more strongly among persons in relationships (vs. single persons). In Study 2, aloneliness was experimentally primed among 93 undergraduates in relationships. When aloneliness was salient (vs. a control), participants reported higher anger and used more pins in a partner‐representative voodoo doll. These results suggest that solitude is an inhibiting factor against anger and, potentially, the perpetration of partner‐directed aggression. Although subsequent work in this area is needed, we add evidence showing the importance of individual differences in the need for solitude.